Cultural pedagogies and human conduct
1 online resource (xviii, 239 pages)
Keywords: "Pedagogy is often glossed as the 'art and science of teaching' but this focus typically ties it to the instructional practices of formalised schooling. Like the emerging work on 'public pedagogies', the notion of cultural pedagogies signals the importance of the pedagogic in realms other than institutionalised education, but goes beyond the notion of public pedagogies in two ways: it includes spaces which are not so public, and it includes an emphasis on material and non-human actors. This collection foregrounds this broader understanding of pedagogy by framing enquiry through a series of questions and across a range of settings. How, for example, are the processes of 'teaching' and 'learning' realised within and across the pedagogic processes specific to various social sites? What ensembles of people, things and practices are brought together in specific institutional and everyday settings to accomplish these processes? This collection brings together researchers whose work across the interdisciplinary nexus of cultural studies, sociology, media studies, education and museology offers significant insights into these 'cultural pedagogies' - the practices and relations through which cumulative changes in how we act, feel and think occur. Cultural Pedagogies and Human Conduct opens up debate across disciplines, theoretical perspectives and empirical foci to explore both what is pedagogical about culture and what is cultural about pedagogy"--